2⁵-3* [ 7*3-2* (6²-2³) : 4 ] + 1²⁰¹³
Răspunsuri la întrebare
Răspuns de
2
2⁵-3* [ 7*3-2* (6²-2³) : 4 ] + 1²⁰¹³
=
=2⁵-3* [ 7*3-2* (2²*3²-2³) : 2² ] + 1 =
=2⁵-3* [ 7*3-2* (2²(3²-2) : 2² ] + 1 =
=2⁵-3* [ 7*3-2*7 ] + 1 =
=2⁵-3* 7 + 1 =
=32-21+1=12
=2⁵-3* [ 7*3-2* (2²*3²-2³) : 2² ] + 1 =
=2⁵-3* [ 7*3-2* (2²(3²-2) : 2² ] + 1 =
=2⁵-3* [ 7*3-2*7 ] + 1 =
=2⁵-3* 7 + 1 =
=32-21+1=12
Răspuns de
1
32-3*[21-2*(36-8)]+1=
=32-3*(21-2*28)+1=
=32-3*(21-56)+1=
=32-3*(-35)+1=
=32+105+1=
=138
=32-3*(21-2*28)+1=
=32-3*(21-56)+1=
=32-3*(-35)+1=
=32+105+1=
=138
Kiramy:
sry am uitat :4
Alte întrebări interesante
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă